The Bonobo and the Behaviorist: Frans de Waal’s Bottom-Up Morality - Diller, James W. (Behav Anal, 2015)
This review considers Frans de Waal’s The Bonobo and the Atheist: In Search for Humanism Among the Primates (2013) from a behavior-analytic perspective. In his book, de Waal asserts evolution as the predominant level of selection for moral behavior, denies the possibility of a prescriptive science of morality, and misrepresents the science of behavior analysis. We expand upon de Waal’s analysis and incorporate operant and cultural levels of selection of moral behavior. We also address the distinction between facts and values and describe behavior-analytic interpretations of belief. In addition, we briefly discuss the possibility of developing a behavior-analytic science of moral behavior.